2023
DOI: 10.3390/su15129617
|View full text |Cite
|
Sign up to set email alerts
|

Pavement Roughness Prediction Using Explainable and Supervised Machine Learning Technique for Long-Term Performance

Kelum Sandamal,
Sachini Shashiprabha,
Nitin Muttil
et al.

Abstract: Maintaining and rehabilitating pavement in a timely manner is essential for preserving or improving its condition, with roughness being a critical factor. Accurate prediction of road roughness is a vital component of sustainable transportation because it helps transportation planners to develop cost-effective and sustainable pavement maintenance and rehabilitation strategies. Traditional statistical methods can be less effective for this purpose due to their inherent assumptions, rendering them inaccurate. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…Studies have demonstrated the ML algorithms' effectiveness in predicting pavement performances [9,30,[52][53][54][55][56][57][58][59][60][61][62][63][64][65][66][67]. Likewise, commonly used algorithms include ANN, SVM and support vector regression (SVR) [40], adaptive boosting (AdaBoost) [68], random forest (RF) [69], gradient boosting decision trees (GBDT) [70], categorical boost (CatBoost) [71], and ensemble models [50].…”
Section: Machine Learning For Iri Predictionmentioning
confidence: 99%
See 3 more Smart Citations
“…Studies have demonstrated the ML algorithms' effectiveness in predicting pavement performances [9,30,[52][53][54][55][56][57][58][59][60][61][62][63][64][65][66][67]. Likewise, commonly used algorithms include ANN, SVM and support vector regression (SVR) [40], adaptive boosting (AdaBoost) [68], random forest (RF) [69], gradient boosting decision trees (GBDT) [70], categorical boost (CatBoost) [71], and ensemble models [50].…”
Section: Machine Learning For Iri Predictionmentioning
confidence: 99%
“…Likewise, Luo et al [61] compared four models-GBDT, XGBoost, SVM, and MLR-to determine the best PPM, finding that GBDT was superior. Sandamal et al [63] employed five ML models-k-Nearest Neighbor (kNN) [74], SVM, DT, RF, and XGBoost-to predict the IRI of pavements on Sri Lankan arterial roads. Focusing on pavement age and cumulative traffic volume as the only predictors, they found that these models outperformed traditional techniques.…”
Section: Machine Learning For Iri Predictionmentioning
confidence: 99%
See 2 more Smart Citations